2018
DOI: 10.3390/molecules23010196
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Total Prenylflavonoids from the Fruits of Psoralea corylifolia L. Prevents Age-Related Cognitive Deficits and Down-Regulates Alzheimer’s Markers in SAMP8 Mice

Abstract: Alzheimer’s disease (AD) is a serious threat for the aging society. In this study, we examined the preventive effect of the total prenylflavonoids (TPFB) prepared from the dried fruits of Psoralea corylifolia L., using an age-related AD mouse model SAMP8. We found that long-term dietary TPFB at 50 mg/kg·day significantly improved cognitive performance of the SAMP8 mice in Morris water maze tests, similar to 150 mg/kg·day of resveratrol, a popular neuro-protective compound. Furthermore, TPFB treatment showed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The level of Akt phosphorylation was observed because Akt is upstream of both the mTOR pathway and GSK-3β pathway. Previous studies have reported that inhibition of the mTOR pathway and GSK-3β pathway ameliorated age-related pathologic changes (Chen et al., 2018; Yuan et al., 2018). The results showed that 6BIO not only inhibits GSK-3β signaling, in concordance with the findings of previous studies (Ko et al., 2018), but also inhibits mTOR signaling, whereas rapamycin inhibits the mTOR pathway but activates GSK-3β signaling via feedback activation of Akt originating from S6K (Wu et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The level of Akt phosphorylation was observed because Akt is upstream of both the mTOR pathway and GSK-3β pathway. Previous studies have reported that inhibition of the mTOR pathway and GSK-3β pathway ameliorated age-related pathologic changes (Chen et al., 2018; Yuan et al., 2018). The results showed that 6BIO not only inhibits GSK-3β signaling, in concordance with the findings of previous studies (Ko et al., 2018), but also inhibits mTOR signaling, whereas rapamycin inhibits the mTOR pathway but activates GSK-3β signaling via feedback activation of Akt originating from S6K (Wu et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…48 It could also effectively prevent age-related cognitive deficit in mice. 49 Moreover, an imbalance between the pro-oxidant and antioxidant produces oxidative stress in the early stage of AD. 50 The generation of ROS and free radicals would cause toxicities to neural cells such as lipid peroxides accumulation, carbonyl proteins disorder, and oxidative DNA damage in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that isobavachalcone significantly inhibits both oligomerization and fibrillization of Aβ 42 . It could also effectively prevent age-related cognitive deficit in mice . Moreover, an imbalance between the pro-oxidant and anti-oxidant produces oxidative stress in the early stage of AD .…”
Section: Discussionmentioning
confidence: 99%
“…PF has been utilized as a conventional Chinese pharmaceutical for well-being supplement fixing [ 24 ]. PF has been reported to contain compounds with molecular diversity, with a few of these displaying estrogen-like, anti-oxidant, osteoblastic, anticancer, antidepressant, anti-inflammatory, hepatoprotective [ 25 ], and antimicrobial activities [ 26 ]. Furthermore, in an AD mouse model, long-term dietary intakes of PF’s total prenylflavonoids (TPFB) at 50 mg/kg day significantly enhanced cognitive function and AD-like neurobiochemical alterations [ 27 ], and could modulate amyloid β-peptide 42 (Aβ42) aggregations in vitro [ 28 ].…”
Section: Introductionmentioning
confidence: 99%